Occupants' satisfaction and perceived productivity in open-plan offices designed to support activity-based working: findings from different industry sectors. Issue 2 (9th March 2021) - Candido, Christhina; Gocer, Ozgur; Marzban, Samin; Gocer, Kenan; Thomas, Leena; Zhang, Fan; Gou, Zhonghua; Mackey, Martin; Engelen, Lina; Tjondronegoro, Dian
Abstract : Purpose: In the rise of offices designed to support activity-based working (ABW), parts of industry have fully transitioned to open-plan environments and then later to unassigned seating, whereas other parts, such as tertiary education, are still in the process of moving away from individual offices. There are a few relevant studies to understand how occupants from industry sectors with different levels of adoption of ABW perceived environments designed to support this way of working. This paper aims to contribute to the knowledge gap by providing insight into workers' satisfaction and dissatisfaction from open-plan offices designed to support ABW along with the key predictors of perceived productivity. Design/methodology/approach: A data set of 2, 090 post-occupancy evaluation surveys conducted in five sectors – tertiary education, finance, construction, property/asset management and design/engineering – was analyzed. ANOVA and confirmatory factor analysis (CFA) were conducted for the survey questionnaires. First, ANOVA tests were conducted for the whole sample with perceived productivity as the dependent variable. A seven-point Likert scale with five theoretical factors was generated with all survey questionnaires. CFA was performed to show the factor loadings. In addition, regression analyses were carried out for each of factor item taken as the independent variable, where perceived productivity was the dependent variable. Key sources of satisfaction and dissatisfaction per sector were analyzed and differences between occupants reporting a negative or positive impact on their productivity were also investigated. Finally, open-ended comments were analyzed to show the key sources of dissatisfaction based on open-ended comments. Findings: Workers from construction were the most satisfied, followed by finance and tertiary education. Occupants from all industry sectors consistently rated their workspaces highly on biophilic and interior design. Distraction and privacy received the lowest scores from all sectors. Open-ended comments showed mismatches between spatial and behavioral dimensions of ABW both for satisfaction and perceived productivity. Interior design was the strongest predictor for perceived productivity for all sectors. Findings dispel the notion that ABW implementation may not be suitable for certain industries, as long as the three key pillars of ABW are fully implemented, including design, behavior and technology. Originality/value: This paper provides insight into workers' satisfaction and dissatisfaction from open-plan offices designed to support ABW in different industry sectors along with the key predictors of perceived productivity.